2022
DOI: 10.1038/s41594-022-00773-z
|View full text |Cite
|
Sign up to set email alerts
|

The cohesin acetylation cycle controls chromatin loop length through a PDS5A brake mechanism

Abstract: Cohesin structures the genome through the formation of chromatin loops and by holding together the sister chromatids. The acetylation of cohesin’s SMC3 subunit is a dynamic process that involves the acetyltransferase ESCO1 and deacetylase HDAC8. Here we show that this cohesin acetylation cycle controls the three-dimensional genome in human cells. ESCO1 restricts the length of chromatin loops, and of architectural stripes emanating from CTCF sites. HDAC8 conversely promotes the extension of such loops and strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 45 publications
(68 reference statements)
2
29
0
Order By: Relevance
“…Our immunoprecipitation data confirm that human cohesin complexes bound to PDS5 do not interact with NIPBL, as suggested by results in yeast [ 31 ]. The competition of NIPBL and PDS5 for binding cohesin appears to be regulated by acetylation [ 51 , 27 ]. This acetylation, in turn, may occur preferentially at CTCF sites, as it is dramatically reduced in Ctcf KO MEFs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our immunoprecipitation data confirm that human cohesin complexes bound to PDS5 do not interact with NIPBL, as suggested by results in yeast [ 31 ]. The competition of NIPBL and PDS5 for binding cohesin appears to be regulated by acetylation [ 51 , 27 ]. This acetylation, in turn, may occur preferentially at CTCF sites, as it is dramatically reduced in Ctcf KO MEFs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This explains why cohesin largely colocalizes with CTCF genome-wide [ 23 , 24 ]. The boundary and/or anchoring function of CTCF depends on its interaction with an interface formed by STAG and RAD21, which is the same that requires WAPL, but possibly also on PDS5 and ESCO1 [ 25 , 26 , 27 , 7 , 13 ]. Recent in vitro reconstitution of loop extrusion by cohesin has demonstrated the requirement for NIPBL to activate the SMC1/3 ATPase [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that all cohesin’s biological functions can be carried out by cohesin in a single acetylated state with ATPase activity either lower (smc3-K112R, K113R smc1-T1117W, or smc3-K113R smc1-D1164E) or higher (smc1-T1117I smc3-K113Q) that wild type. One possibility is that the ATPase and its biological functions are controlled by an additional regulatory protein like Pds5p (Bastié et al 2022; van Ruiten et al 2022). However, invoking redundancy avoids the question of what is the fitness advantage for the acetylation-dependent control of cohesin’s ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…1A). A recent study suggested that Smc3p-K113 acetylation inhibited Scc2p binding to cohesin indirectly by stabilizing the binding of Pds5p, which then precluded Scc2p binding (Bastié et al 2022; van Ruiten et al 2022). However, a more direct mechanism was suggested by the observation that Scc2p stimulation of cohesin ATPase activity in vitro is drastically reduced by a mutation that mimics acetylation by substituting glutamine for K113 (K113Q) (Murayama and Uhlmann 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cohesin, stimulated by NIPBL, acts as an adenosine triphosphate (ATP)dependent molecular motor extruding DNA and folding the genome into topologically associated domains (TADs) (10)(11)(12)(13). Removing either PDS5 or WAPL stabilizes cohesin binding to chromatin and can alter TAD structure in different ways (4,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%